2013
DOI: 10.1109/jphot.2013.2281611
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Fiber $N \times 1$ Multimode Combiner

Abstract: Fiber-based multimode combiners allow for wavelength and power scaling of laser sources while maintaining a common emission aperture and divergence. For applications in the mid-infrared spectral band, chalcogenide glass optical fibers are one of the few alternatives with high-power beam delivery. We demonstrated a 7 Â 1 multimode fiber combiner based on a sulfide-based multimode chalcogenide fiber with 9 76% per-port transmission. Wavelength combining and power scaling in the mid-infrared are demonstrated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Both applications are of particular interest in the mid-wave and long-wave infrared wavelength ranges. Gattass et al [19] fabricated 7 × 1 infrared fiber optic multimode combiner based on an arsenic sulfide infrared fiber with transmission over a wide range of infrared wavelengths ( Fig. 5(a)).…”
Section: Fiber-based Multimode Beam Combinersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both applications are of particular interest in the mid-wave and long-wave infrared wavelength ranges. Gattass et al [19] fabricated 7 × 1 infrared fiber optic multimode combiner based on an arsenic sulfide infrared fiber with transmission over a wide range of infrared wavelengths ( Fig. 5(a)).…”
Section: Fiber-based Multimode Beam Combinersmentioning
confidence: 99%
“…(a) 7 × 1 infrared fiber optic multimode combiner based on an arsenic sulfide infrared fiber and (b) the spectral output of the sources separately (top) and combined (bottom)[19].…”
mentioning
confidence: 99%
“…For infrared fibers, the Naval Research Laboratory has pioneered this field by demonstrating N × 1 chalcogenide-fiber based combiners [14]. Figure 1 shows an example of a packaged 7 × 1 device with the inset showing the hexagonal arrangement of the cores (shown in dark).…”
Section: A Fiber Couplers Splitters Combinersmentioning
confidence: 99%
“…Reported values for the As 2 S 3 combiner exceeded 76% per port with champion numbers above 90%. The same fiber combiner architecture can be used for wavelength combination, with the output of multiple midinfrared quantum cascade laser sources and a 2 μm diode laser being combined into a single output [14].…”
Section: A Fiber Couplers Splitters Combinersmentioning
confidence: 99%
“…So far, successful splicing with silica fiber has been demonstrated [16]. Chalcogenide glass fiber devices have been demonstrated that allow for beam combining of QCLs [17] and imaging for MIR [18]. Optical attenuators have been demonstrated [19].…”
Section: Introductionmentioning
confidence: 99%